(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Antidepressants are frequently used in outpatient department in psychiatric hospitals, but prescription patterns may not be according to international guidelines in low-and middle-income countries (LMICs). There is a paucity of data regarding the results of Bangladesh data, especially in the tertiary care hospitals. The aim of the study is to observe the prescription pattern of antidepressants in the outpatient department of psychiatry in two tertiary care hospitals in Bangladesh .Methods: This was a cross-sectional descriptive study conducted in Dhaka Medical College Hospital (DMCH) and the National Institute of Mental Health (NIMH). We collected a total of 760 prescriptions (380/ prescription per hospital) using the systematic consecutive sampling technique. Analysis is based on descriptive statistics and Chi-Square tests. Results: Of the 760 respondents, 55.9% were male and 44.1% were female; 63.5% were 16–35 years of age. The most frequent were schizophrenia (16.4%), anxiety disorders (15.9%) and bipolar disorder (9.3%), but no diagnosis was recorded for 28.2% of the prescription antidepressants. Overall, 47.8% received an antidepressant. The Class of selective serotonin reuptake inhibitors (SSRIs) was the most common (62.7%), and sertraline (33.0%) and escitalopram (29.7%) were the most common agents. Both tricyclic antidepressants (5.8%) and other newer agents (5.9%) were less commonly used. Polypharmacy was detected in 21.2% of antidepressant users, the combination of sertraline and clomipramine being the most frequent two-drug combination (5.8%). The prescription practice of SSRI monotherapy varied significantly between hospitals, with higher rates at DMCH (21.3% vs 8.8%, p<0.001) and lower rates at NIMH for TCAs (2.1% vs 0.8%). Conclusion: High polypharmacy, irrational use of generics, and lack of record keeping suggest the necessity of prescriber education, drug utilisation review, and enforcement of regulatory policies to ensure rational prescribing. Bangladesh J Medicine 2026; 37(1): 52-57